Novel turbine rotor shroud film-cooling design and validation, part 2 - Chana, K; Haller, B (2009)
This paper is part two of a two part paper which considers a shroud film-cooling system design. The design was carried out using test results from a previous two-dimensional (2D) design and optimisation using three-dimensional (3D) CFD. The first cooling design was carried out using a streamline boundary layer approach and tested in the QinetiQ turbine test facility (TTF). The test results showed the design did not function as well as had been predicted and gave a poor performance in terms of film cooling effectiveness. Lessons learnt from the 2D design as well as understanding gained from heat transfer and pressure data taken on the rotor casing led to the formulation of a completely new design philosophy. Accepting, cooling films would not survive rotor passing and therefore concentrating on localised cooling as well as the re-establishment of cooling films between rotor passings. The design concept was validated/optimised with the aid of 3D CFD. Heat transfer instrumentation was implemented in a cooling insert fitted over the test rotor to evaluate the performance of the design. Tests carried out with and without cooling showed an improvement in cooling performance, leading to a 40% reduction in heat transfer rate to the rotor casing across the rotor overtip region. A significant improvement was achieved with the new design over the original with reductions in casing heat transfer rates of up to 44%, with a design coolant mass flow of 1.85% of core flow. Heat transfer data were successfully processed to Nusselt number, allowing the results to be translated to a gas turbine engine design. Copyright © 2009 by ASME.